PARWA DATA CANDRABHANU DAN PEPARIKAN DATA CANDRABHANU: SEBUAH KAJIAN INTERTEKSTUALITAS - Ayu Juniantari, Ni Nyoman (Humanis, 2015)
Research Parwa Data Candrabhanu and Peparikan Data Candrabhanu aims to uncover the intertextual relationships and meanings contained in the two texts. Transformation Parwa Data Candrabhanu and Peparikan Data Candrabhanu story this incident involving linkage, plot, character and characterization, setting, theme and mandate as well as reveal the difference between the two, after that proceed to give a description of the meaning contained in the two texts. At the end of this study can be seen that the transformation in Parwa Data Candrabhanu and Peparikan Data Candrabhanu done well despite the addition and subtraction in Peparikan Data Candrabhanu. ........... This study is based on the structural theory proposed by Teeuw, intertextual theory proposed by Kristeva and semiotic theory advanced by Sudjiman. The method used in this study is a descriptive analytic method assisted with translation techniques to facilitate the analysis according to the problem under study. ........... From this analysis it can be concluded that the story of parwa and peparikan has prominent similarities in terms of the similarity of the story to the characters names. The equation is a main character named Prabhu Data Candrabhanu who has a wife named the Dewi Wirasanti and have a beautiful daughter named Diah Somawati. All three are said to be very powerful because of its success in yoga and meditation believed to hold fast to the teachings of Buddhism Bairawa. In addition to having equality, parwa and peparikan story also have differences. The difference if the parwa story is told through Hastinapura victory against Tasikmalaya, another case in peparikan story, Arjuna is told to lose the war, then decided to return to Hastinapura, and want to attack the country of Tasikmalaya. In addition to uncovering intertextual relationship of the second story, this study also revealed the meaning contained in these two stories. These include the meaning and spiritual significance Bairawa Buddha.
Keywords: Parwa, Peparikan, Intertextual